Conference hybrid event as a new alternative event in the covid-19 pandemic - Firmansyahrani, Sherinatasha; Younna, Syifa; Vanessa, Vanessa; Noor, Any (Institut Pariwisata dan Bisnis Internasional, 2022)
COVID-19 pandemic has a very large impact in various fields, one of which is in the MICE event field, especially conference events. Since there are no activities that require gathering many people around in one place. However many event organizers are looking for a strategies that related to organising an event during this pandemic, one of which is holding a conference event using a hybrid concept by implementing the technology and CHSE health protocols to minimize the spread of coronavirus. This article which focuses on desk study begins with collecting data from secondary data through the internet. The data is developed according to the list of preparing the hybrid event concept and then the data is displayed into a conference hybrid event project. The result of this study will be in the form of concept how to hold a hybrid conference event by implementing the CHSE health protocol. This project is expected to be especially useful for the organizers of organizing MICE events during the COVID-19 pandemic.